Reassessment of the age and depositional environment of the Kirkgecit Formation based on larger benthic foraminifera, NW Elazig, Eastern Turkey - Kaygili, Sibel (Tubitak Scientific & Technological Research Council Turkey, 2021)
The middle-upper Eocene Kirkgecit Formation, the fossil content of which is the subject of this study, is deposited in a back-arc basin controlled by block-faulting. The Kirkgecit basin is interpreted as being formed under an extensional regime related to convergence between the Anatolian plate in the north and the Arabian plate in the south. The aim of this study is to reassess the age and depositional environment of the Kirkgecit Formation by using detailed biometric analysis data obtained from the reticulate Nummulites and determinations of other larger benthic foraminifera (LBF) in the unit. For this purpose, two sections were measured from the latest Bartonian-Priabonian aged unit. Biometric data of the Nummulites hormoensis and Nummulites fabianii from the Kirkgecit Formation exposures in the northwest of Elazig has been presented for the first time. In general, Nummulites fabianii has robust test with thick walls, while Nummulites hormoensis has elongated test with thinner walls in relation to the increase of water depth. The change in embryon size of these reticulate Nummulites has been considered an important indicator for evolution and biostratigraphy. Nummulites hormoensis marks latest Bartonian to early Priabonian (SBZ 18) while Nummulites fabianii is a marker for middle-late Priabonian (SBZ 19-20). The Kirkgecit Formation in the study area was previously dated as late Lutetian-Priabonian based on LBF of it. However, by considering the LBF determined in this study, the latest Bartonian-Priabonian age was assigned to unit. Based on the paleontological and sedimentological features, the Kirkgecit Formation has been interpreted as a unit deposited on the inner and middle parts of a shallow ramp.
Keywords: Kirkgecit Formation; latest Bartonian-Priabonian; eastern Turkey; reticulate Nummulites; biometry; paleoenvironment